Perbandingan Agility Antara Pemain Badminton GandaPutra Dan Bola Voli Putra - Imama, Ilham Shyko; , Wijianto, ST, M.Eng, Sc (2017)
Background: agility or also called agility is the ability to change body position or direction of movement of the body quickly when you're moving fast withoutlosing balance or awareness of body position. In this agility components alreadyincluded elements of dodge quickly, changing the position of the body rapidly,moving then stopped and continued to move as soon as possible. everyone wants to have high agility of this means agility different people depending on how heincluded his regularity, discipline, in dependence by the food and nutrition andother factors. Objective: to know the agility Comparison between players badminton men'sdoubles and men's volleyball.Methods: This study using purposive sampling method with two research approaches and post-test group. The number of samples in this study were 30samples of same-sex male men's doubles badminton players as many as 15 peopleand men's volleyball player of 15 people. Agility each player will be measured using illinois agility test. Illinois agility test is a standard test to measure the levelof agilityResults: Statistical test using the Shapiro-Wilk test. Difference difference testusing Independent t - test showed p: 0.028 (p <0.05). Statistical test resultsshowed a difference between the level of agility of players badminton men'sdoubles and men's volleyball.Conclusion: There is a difference between a player agility badminton men'sdoubles and men's volleyball. With agility level badminton players higher than themen's doubles, men's volleyball players between the level of agility of playersbadminton men's doubles and men's olleyball. With the level of agility men'sdoubles badminton players are superior than the men's volleyball player Keywords: Agility, player badminton men's doubles, men's volleyball player